Intrinsically Photoswitchable α/β Peptides toward Two‐State Foldamers. Issue 32 (15th July 2018) - Marafon, Giulia; Crisma, Marco; Moretto, Alessandro
Abstract: A simple, unsaturated, E – Z photoisomerizable β‐amino acid, ( Z )‐3‐aminoprop‐2‐enoic acid, has been introduced into peptide foldamers through a one‐pot chemical coupling, based on Pd/Cu‐catalyzed olefin oxidative amidation, between two peptide segments carrying, respectively, a ‐Gly‐NH2 residue at the C‐terminus and an acryloyl group at the N‐terminus. Reversible conversion between the Z and E configurations of the 3‐aminoprop‐2‐enoic linkage was achieved photochemically. A crystallographic analysis on two model compounds shed light on the consequences, in terms of 3D structure and self‐association properties, brought about by the different configuration of the unsaturated linkage. As a proof of concept, E – Z photoisomerization of a 3‐aminoprop‐2‐enoic acid residue, inserted as the junction between two conformationally distinct peptide domains (one helical while the other β‐sheet promoter), allowed supramolecular self‐association to be reversibly turned on/off. Abstract : Photoswitchable junctions : A simple unsaturated β‐amino acid has been introduced into peptide foldamers through a one‐pot chemical coupling between two peptide segments carrying, respectively, a primary amide at the C‐terminus and an acryloyl group at the N‐terminus. This novel type of ligation gives access to peptidomimetics and foldamers with photochemically tunable 3D structure and self‐association tendency.